Beginning VB 2005 Databases - Huddleston, James (Apress, 2012)
This book is for anyone interested in how to access relational data with VB. Only a bit of experience with VB is assumed, and no prior experience with relational databases or the relational database language SQL is required. We cover all fundamentals carefully and in an order we believe leads easily from one topic to another, building knowledge and experience as you progress through the book. So, chapters are best read in sequence.